Footloose global value chains: How trade costs make a difference - Adam Jakubik; Victor Stolzenburg (World Trade Organization (WTO), 2019)
The geography of global value chains (GVCs) depends crucially on trade costs between countries hosting various stages of production. Some stages might be more sensitive to trade costs than others. In this paper, we exploit a value-added decomposition of bilateral trade flows to distinguish low value-added GVC trade typically associated with production stages such as assembly, from high value-added GVC trade associated with stages such as R&D and design. We test the hypothesis that low value-added stages will more easily reroute given changes in trade costs between importing and exporting countries than high value-added stages. The intuition for this hypothesis is that trade costs accumulate with multiple border crossings and are larger relative to the profit margins in low value-added stages. Furthermore, high value-added stages often require larger fixed cost investments which are often highly relationship-specific and knowledge-intensive, making them harder to relocate. We find strong empirical support for our hypothesis. This observation has important implications for development policies and bilateral trade policies aimed at reducing imbalances by repatriating offshored production stages.
Keywords: C23; L23; F13; 330; value added trade; trade costs; organisation of production